Evaluation of a Long-Distance IEEE 802.11ah Wireless Technology in Linux Using Docker Containers - Daniils Aleksandrovs-Moisejs; Aleksandrs Ipatovs; Elans Grabs; Dmitrijs Rjazanovs (Elektronika ir Elektrotechnika, 2022)
Wireless technologies are essential for modern people to maintain uninterrupted connection to the Internet. The most popular standards for wireless technologies are standards of the IEEE 802.11 family. Currently, data transmission rate achievable by IEEE 802.11ac or 802.11ax standards can reach up to 10 Gbit/s. Different IEEE standards have specific data transmission rates. For example, the IEEE 802.11ah standard or Wi-Fi HaLow (code name) operates in the 900 MHz band, which is an unlicensed frequency band below 1 GHz, and is called the “Sub-1-GHz” range. In theory, this standard can provide coverage range of up to 543 meters indoors and data transfer rate of up to 347 Mbit/s (using a maximum of four spatial streams and 16 MHz channel bandwidth). The great benefit of the 802.11ah standard is low energy consumption, which enables communication between devices from the Internet of Things (IoT) over long distances without using a lot of energy. The Wi-Fi HaLow standard is being studied by the authors of the presented article in the ns-3 network simulation program with the 802.11ah module installed and implemented in Docker containers, VirtualBox Virtual Machines (VMs) with a running Linux operating system. During the simulations, results were obtained for the Docker containers simulation with a limited number of stations over different simulation times. These results have been studied in different scenarios. In the scenarios, the results of the Wi-Fi HaLow network simulation were converted into another simulation time, and thus were compared with each other.